1975
DOI: 10.1113/jphysiol.1975.sp011114
|View full text |Cite
|
Sign up to set email alerts
|

Mean and breath‐by‐breath pattern of breathing in man during steady‐state exercise.

Abstract: SUMMARY1. The breathing pattern, that is the relation between tidal volume (VT) and the inspiratory (T1) and expiratory (TE) durations, has been studied for individual breaths (forty in each steady state).2. Five healthy subjects were studied in steady-state exercise on a bicycle ergometer breathing air; three of them were also studied in hypercapnia, at rest and during exercise, and two of them also during exercise on a treadmill.3. Tidal volume and respiratory frequency both increased with work load. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 17 publications
1
35
1
Order By: Relevance
“…Newsom Davis & Stagg, 1975; see also Fig. 3 of Kay et al 1975) was significant in only the minority of subjects who showed a large amount of scatter: even in them it was demonstrable in only some of the runs. In Fig.…”
Section: Expirationmentioning
confidence: 99%
“…Newsom Davis & Stagg, 1975; see also Fig. 3 of Kay et al 1975) was significant in only the minority of subjects who showed a large amount of scatter: even in them it was demonstrable in only some of the runs. In Fig.…”
Section: Expirationmentioning
confidence: 99%
“…When VT is high the slopes of the VT, Tj and TE relations are at a maximum (Kay et al 1975) and the breath-by-breath variation gives rise to a lot of scatter that could mask any small trend that might underlie the mean values. However, other factors may be involved in some types of step: thus the gross changes seen at the off-transient in Fig.…”
Section: Patterningmentioning
confidence: 99%
“…For all subjects the data from each transition were plotted on the VT-TE-TI modified von Euler plot' (Kay, Petersen & Vejby-Christensen, 1975). There were no consistent patterns even within subjects; the changes in VE took the form primarily of changes in VT rather than of frequency, with TE varying, if anything, more than T1, and independently of it.…”
Section: Pattern Of Breathingmentioning
confidence: 99%
“…Although humans show some flexibility in locomotor-respiratory coupling (Bechbache & Duffin, 1977;Bramble & Carrier, 1983;Paterson, Wood, Morton & Henstridge, 1986;Loring, Mead & Waggener, 1990), quadrupeds, notably horses, almost invariably take one breath per stride at canter and gallop over a wide range of speeds (Bramble & Carrier, 1983;Butler et al 1993b). At trot, a definite but rather variable and inconstant entrainment has also been observed in horses (Bramble 1989;Art, Desmecht, Amory & Lekeux, 1990;Lafortuna & Saibene, 1991 (Hey, Lloyd, Cunningham, Jukes & Bolton, 1966;Kay, Strange-Petersen & Vejby-Christensen, 1975b;Cunningham, Robbins and Wolff, 1986). This possibly results from respiratory control mechanisms geared to a principle of energy optimization (Otis, Fenn & Rahn, 1950;Mead, 1960;Priban & Fincham, 1965;Yamashiro, Dubenspeck, Lauritsen & Grodins, 1975 The expansion of this tube ranged from a minimum of 045 m to a maximum of 5.7 m. The minimum volume of the total VD thus obtained was 7-3 1 (fully compressed) and the maximum was 66-7 1 (fully extended).…”
mentioning
confidence: 99%